2014
DOI: 10.1038/nchem.2005
|View full text |Cite
|
Sign up to set email alerts
|

Vibronic coherence in oxygenic photosynthesis

Abstract: Photosynthesis powers life on our planet. The basic photosynthetic architecture consists of antenna complexes that harvest solar energy and reaction centres that convert the energy into stable separated charge. In oxygenic photosynthesis, the initial charge separation occurs in the photosystem II reaction centre, the only known natural enzyme that uses solar energy to split water. Both energy transfer and charge separation in photosynthesis are rapid events with high quantum efficiencies. In recent nonlinear s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
411
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 389 publications
(429 citation statements)
references
References 39 publications
18
411
0
Order By: Relevance
“…In the 2D ES spectra of FCP we would expect coherences of various origins and amplitudes to appear: ground state vibrational coherences of Chl a, Chl c and Fx, excited state vibronic coherences of the same frequencies, mixed coherences of shifted or combinational frequencies 16,45 and electronic coherences due to excitonic coupling of chlorophylls. Such distinction between the coherences of different origin is conveniently observed in the Fourier amplitude maps.…”
Section: A Identification Of Coherencesmentioning
confidence: 99%
See 2 more Smart Citations
“…In the 2D ES spectra of FCP we would expect coherences of various origins and amplitudes to appear: ground state vibrational coherences of Chl a, Chl c and Fx, excited state vibronic coherences of the same frequencies, mixed coherences of shifted or combinational frequencies 16,45 and electronic coherences due to excitonic coupling of chlorophylls. Such distinction between the coherences of different origin is conveniently observed in the Fourier amplitude maps.…”
Section: A Identification Of Coherencesmentioning
confidence: 99%
“…The energy gap of 715 cm −1 is close to the strongest vibrational Chl a mode of 745 cm −1 , thus allowing for electronic-vibrational resonance [55][56][57] . Recently, specific vibrational modes were suggested to speed up the initial charge transfer step in the photosystem II (PS II) reaction center 16,17 . Finally, this does not contradict our previous suggestion that Chl c is coherently coupled to Chl a 12 , however, the coherent mechanism may be far more complicated and calls for future studies.…”
Section: B Ultrafast Chl C-chl a Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of experimental studies suggested the possibility of active engagement of molecular vibrational excited states in charge separation [1][2][3] . In a pump-push experiment on organic photo-voltaic cells, Bakulin et.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In addition to the (often low frequency) continuum, the environmental spectral densities of pigment-protein complexes are generally structured; that is, there are specific underdamped vibrational modes of the environment that couple strongly to the excitonic degrees of freedom. There is now increasing evidence to suggest that these underdamped modes are an important contributing factor to the long-lived coherences observed in photosynthetic systems, [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] as well as links between the quantum mechanical nature of these vibrational modes and enhanced transfer rates. 25,37,39,40 A multitude of powerful computational methods have been developed to deal with the difficulties faced in modelling strongly dissipative quantum systems.…”
Section: Introductionmentioning
confidence: 99%